The Role of high flow nasal therapy in Intensive Care Units - Wyszkowski, Michał; Jaremek, Anna; Kępa, Joanna; Kandefer, Norbert; Grabarczyk, Aleksandra; Pawlak, Anna; Grad, Sylwia; Gregorek, Małgorzata; Gregorek, Paweł (Journal of Education, Health and Sport, 2023)
Introduction and purpose: High Flow Nasal Therapy is quite new respiratory support method, although recently it became more popular – especially during COVID-19 pandemic. Physiological mechanisms as well as main applications were observed and described in several randomized controlled trias and metaanalisys. The purpose of this review is to present fundamental studies and indicate applications of this method. Brief description of the state of knowladge: Breathing mixture with a maximum flow 60l/min needs to be heated and humidified to protect the airways from dryness. Optimal humidity improves mucocilary clearance, reduces inflammation of the airways and energy expenditure, especially in acute respiratory failure. High flow nasal therapy may imrpove the mechanics of breathing also by washout of nasopharyngeal dead space and generating positive airway pressure during exhalation, which keeps airways open and prevents the alveoli from collapsing. High flow therapy can be use in many different applications but at Intensive Care Unit the most important are: acute hypoxemia, during extubation or rest breaks from NIV. It is important to monitor the patient and predict the need for intubation on time. There are physiological states that we shoud focus on: respiratory rate, dyspnea or work of breathing, but it is good to know ROX index which can be helpful to assess the success of the therapy. Summary (conlcusions): High flow nasal therapy is a simple and safety respiratory support method that can be applicable at Intensive Care Units. It can lower the intubation numbers and help during NIV rest breaks. High flow nasal therapy is a very promising method for all patients with respiratory failure but it is important to monitor the patient and not delay the intubation.